Cardiovascular Pharmacological Support Among Preterm Infants in Chinese Referral Center Neonatal Intensive Care Units - Luo, Ningxin; Jiang, Siyuan; McNamara, Patrick J.; Li, Xiaoying; Guo, Yan; Wang, Yang; Han, Junyan; Deng, Yingping; Yang, Yi; Lee, Shoo K.; Cao, Yun (Frontiers in Pediatrics, 2021)
Objective: To describe cardiovascular pharmacological support in infants born at <34 weeks' gestation within the first postnatal week in Chinese neonatal intensive care units (NICUs). Design: A secondary analysis of data from a multicenter randomized controlled study (REIN-EPIQ). A questionnaire regarding cardiovascular support practices was also completed by all participating NICUs. Setting: Twenty-five tertiary hospitals from 19 provinces in China. Patients: All infants born at <34 weeks' gestation and admitted to participating NICUs within the first postnatal week from May 2015 to April 2018 were included. Infants who were discharged against medical advice were excluded. Measures and Main Results: Among the 26,212 preterm infants <34 weeks, 16.1% received cardiovascular pharmacological support. The use rates increased with decreasing gestational age and birth weight, with 32.5% among infants <28 weeks and 35.9% among infants <1,000 g. Cardiovascular pharmacological support was independently associated with higher risks of death (aOR 2.8; 95% CI 2.4–3.3), severe intraventricular hemorrhage (IVH) (aOR 2.1; 95% CI 1.8–2.5) and bronchopulmonary dysplasia (BPD) (aOR 2.2; 95% CI 2.0–2.5). Overall 63.1% courses of cardiovascular pharmacological support were >3 days. Prolonged cardiovascular pharmacological support (>3 days) was independently associated with lower rates of survival without morbidity in very-low-birth-weight infants, compared with infants with shorter durations. Dopamine was the most commonly used cardiovascular agent. The cardiovascular pharmacological support rates varied from 1.9 to 65.8% among the participating NICUs. Conclusions: The rate of cardiovascular pharmacological support within the first postnatal week was high with prolonged durations in Chinese NICUs. Marked variation in cardiovascular support existed among participating NICUs. Cardiovascular pharmacological support during the early postnatal period, especially prolonged, may be associated with adverse neonatal outcomes. Clinical Trial Registration: The original trial was registered as “Reduction of Infection in Neonatal Intensive Care Units using the Evidence-based Practice for Improving Quality” (ID: NCT02600195) on clinicaltrials.gov. https://clinicaltrials.gov/ct2/show/NCT02600195?term=NCT02600195&draw=2&rank=1.